Making STEM Equitable: An Active Learning Approach to Closing the Achievement Gap - Burke, Christian; Luu, Richard; Lai, Andy; Hsiao, Valerie; Cheung, Elwin; Tamashiro, Dustin; Ashcroft, Jared (International Journal of Active Learning, 2020)
Active learning is a pedagogical approach which engages students in the learning process, aiming to optimize comprehension of educational material. Meta-analysis of current research shows maximum impact when applied to STEM education, especially for underrepresented minority (URM) students and students with a low GPA. This study focuses on student success, progression, completion and STEM interest within the General Chemistry course sequence at Pasadena City College, which has a 51% Hispanic student population. Data from classes implementing active learning pedagogy consistently had higher success and progression rates, as well as increased progression success from General Chemistry 1 to General Chemistry 2, with a greater positive impact and completion success among Hispanic students compared to students from Asian populations, whose progression success was negatively impacted through use of active learning pedagogy in comparison to traditional lecture-based coursework. Comparison of scores for the American Chemical Society General Chemistry Exams, from this community college and at a national level, indicates active learning students perform equally well on chemistry standardized tests. In total, active learning classes were most beneficial to Hispanic students, and should be designed according to course level, be scaffolded to future coursework to maximize impact through development of STEM active learning pathways in which students are immersed in active learning classrooms continuously through undergraduate STEM academic coursework.